Stable Domain Assembly of a Monomolecular DNA Quadruplex: Implications for DNA-Based Nanoswitches - Kankia, Besik (Biophys J, 2016)
In the presence of K(+) ions, the 5′-GGGTGGGTGGGTGGG-3′ (G3T) sequence folds into a monomolecular quadruplex with unusually high thermal stability and unique optical properties. In this study we report that although single G3T molecules unfold and fold rapidly with overlapping melting and refolding curves, G3T multimers (G3T units covalently attached to each other) demonstrate highly reproducible hysteretic behavior. We demonstrate that this behavior necessitates full-length tandem G3T monomers directly conjugated to each other. Any modification of the tandem sequences eliminates the hysteresis. The experimentally measured kinetic parameters and equilibrium transition profiles suggest a highly specific two-state transition in which the folding and unfolding of the first G3T monomer is rate-limiting for both annealing and melting processes. The highly reproducible hysteretic behavior of G3T multimers has the potential to be used in the design of heat-stimulated DNA switches or transistors.